The FtcR-Like Protein ActR in Azorhizobium caulinodans ORS571 Is Involved in Bacterial Motility and Symbiosis With the Host Plant - Sun, Li; Wang, Dandan; Yin, Zhiqiu; Zhang, Chengsheng; Bible, Amber; Xie, Zhihong (Frontiers in Microbiology, 2021)
Bacterial signal transduction pathways are important for a variety of adaptative responses to environment, such as two-component systems. In this paper, we reported the characterization of a transcriptional regulator in Azorhizobium caulinodans ORS571, ActR, with a N-terminal receiver domain and one C-terminal OmpR/PhoB-type DNA binding domain. Sequence analysis showed that ActR shared a high similarity with FtcR regulator of Brucella melitensis 16M known to be involved in flagellar regulation. The structural gene of this regulator was largely distributed in Alphaproteobacteria, in particular in Rhizobiales and Rhodobacterales and that was located within clusters of genes related to motility functions. Furthermore, we studied the biological function of ActR in A. caulinodans grown at the free-living state or in association with Sesbania rostrata by constructing actR gene deletion mutant. In the free-living state, the bacterial flagellum and motility ability were entirely deleted, the expression of flagellar genes were down-regulated, the exopolysaccharide production, biofilm formation and cell flocculation decreased significantly compared with those of the wild type strain. In the symbiotic state, △actR mutant strain showed weakly competitive colonization and nodulation on the host plant. These results illustrated that FtcR-like regulator in A. caulinodans is involved in flagellar biosynthesis and provide bacteria with an effective competitive nodulation for symbiosis. These findings improved our knowledge of FtcR-like transcriptional regulator in A. caulinodans.